Numerical analysis of fibre reinforced polymer retrofitted masonry panels - Luccioni, Bibiana Maria (2012)
The numerical analysis of the in-plane mechanical behaviour of unreinforced and carbon fibre reinforced polymer (CFRP) retrofitted masonry walls, using a coupled damaged-plasticity model, is presented in this paper. The comparison of numerical and experimental results shows the model ability to simulate the inplane behaviour of masonry elements retrofitted with CFRP. Numerical analyses are carried out to verify the efficiency of the reinforcement with CFRP. Finally, the in-plane behaviour of real scale retrofitted walls is reproduced.